2015
DOI: 10.15414/jmbfs.2015.4.special2.23-25
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Glu-1 in European Wheat Genetic Resources and Varieties

Abstract: Keywords: Storage proteins, HMW -GS, Triticum aestivum L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Protein sizing with the chip-based protein analysis system was performed by running the protein sizing standard on each chip from a designated well. Following the analysis of this sizing standard, the software generated a standard curve of the measured migration time versus the known molecular weight of each standard protein which was used to determine the size of each of the proteins detected within the sample (Kuschel et al, 2002). Internal standards, the lower and upper marker, were included in each sample.…”
Section: Resultsmentioning
confidence: 99%
“…Protein sizing with the chip-based protein analysis system was performed by running the protein sizing standard on each chip from a designated well. Following the analysis of this sizing standard, the software generated a standard curve of the measured migration time versus the known molecular weight of each standard protein which was used to determine the size of each of the proteins detected within the sample (Kuschel et al, 2002). Internal standards, the lower and upper marker, were included in each sample.…”
Section: Resultsmentioning
confidence: 99%
“…The possible reason for the higher polymorphism of storage proteins obtained for SDS -PAGE in the present study could be due to relatively high genetic diversity of HMW -GS. (Chňapek et al, 2013(Chňapek et al, , 2014Gregová et al, 2000;Kuťka Hlozáková et al, 2015;Oslovičová et al, 2010;). Some previous studies based on protein profile demonstrated that numbers of cultivars are indistinguishable (Marchylo and LaBerge, 1981;Shewry et al, 1978), because of that Ahmed et al (2010), Fouda et al (2011) and Shehata (2004) used also DNA marker such as RAPD to differentiate wheat genotypes.…”
Section: Rapd -Pcrmentioning
confidence: 99%
“…The aim of the present study was to provide molecular patterns for the identification and characterization of the phylogenetic relationships among twentyfour European cultivars of common wheat, included the genotype with probably novel highmolecularweight glutenin subunits (HMW -GS) identified by SDS -PAGE (Kuťka Hlozáková et al, 2015). This will be helpful in future for genomic mapping studies leading to obtain improved crop productivity with fresh genetic background.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that A × 2* and D × 5 + Dy10 is associated with good bread-making quality, especially dough strength, while D × 2 + Dy12 is associated with poor quality. The highest polymorphism of HMW-GS is regularly detected on 1B chromosome [ 4 , 5 , 6 , 7 ]. Nowadays, the most challenging task for wheat breeders is not only to increase grain yield [ 8 ] but also to improve the grain quality for end products.…”
Section: Introductionmentioning
confidence: 99%